Ethnopharmacology Study of Plants from Atlantic Forest with Leishmanicidal Activity - Santos, Beatriz Mendes [UNESP]; Bezerra-Souza, Adriana [UNESP]; Aragaki, Sonia; Rodrigues, Eliana; Umehara, Eric; Ghilardi Lago, João Henrique; Laurenti, Márcia Dalastra; Ribeiro, Susan Pereira; Passero, Luiz Felipe Domingues [UNESP] (Hindawi, 2019)
Leishmaniasis is an infectious disease caused by a protozoan belonging to Leishmania genus. Different clinical outcomes can be observed depending on the parasite species and patient's health condition. The outcomes can range from single cutaneous lesions to lethal visceral form. The treatment of all forms of leishmaniasis is based on pentavalent antimonials, and, in some cases, the second-line drug, amphotericin B, is used. Beside the toxicity of both classes of drugs, in some areas of the world, parasites are resistant to antimonial. These detrimental features make fundamental the discovery and characterization of new drugs or plant extracts with leishmanicidal effects. Brazil is a well-known country for its biodiversity. Additionally, the common knowledge inherited for generations in small villages makes Brazil a source of new information and resources for the discovery and development of new drugs. Based on ethnopharmacology, elderlies were interviewed about plants they commonly used for skin diseases and infections. Five native plants from Atlantic forest were indicated; EtOH and n-hexane extracts were prepared with the vegetative organs of the plants and assayed against promastigote and amastigote forms of L. (L.) amazonensis. The major molecules of each extract were detected using qualitative nuclear magnetic resonance. Among all tested extracts, the n-hexane extract from the leave of Eugenia uniflora (Myrtaceae), enriched in myricitrin and quercitrin flavonoids, was the most effective against L. (L.) amazonensis amastigotes. This data supports the ethnopharmacology approach as a successful tool for the discovery of new drugs with leishmanicidal effects.